Chemical approach to contact dermatitis caused by household products. I. N-isopropyl-N'-phenyl-p-phenylenediamine in heavy duty rubber gloves - Kaniwa Masa-Aki; 6aNakamura Akitada; Kojima Shigeo (Eisei Kagaku (Japanese Journal of Toxicology and Environmental Health), 1982)
Japanese article with English abstract
Keywords: Allergic contact dermatitis; Determination of antioxidants; Heavy duty rubber gloves; N-isopropyl-N-phenyl-p-phenylenediamine5Styrenated phenol; Patch testing